Perbedaan Cakupan Imunisasi Polio Pada Bayi Antara Puskesmas Di Desa Dan Di Kota Di Kabupaten Sukoharjo Periode Juli 2015 Sampai Juni 2016 - Ardiyanto, Afrizal; , Prof. Dr. Bambang Soebagyo, dr. Sp.A (K) (2017)
Immunization is one form of effective health interventions in reducing morbidity and infant mortality. So this is one of the main priorities of government in health care, especially in the field of preventive health centers. Government efforts to free Indonesia from Polio is to conduct Polio Eradication Programme (ERAPO) and National Immunization Week (PIN) Polio which aims to increase the number of Polio immunization coverage that already exists. To analyzing the differences of Polio Immunization coverage in infants between health centers in rural and urban areas in Sukoharjo during the period of July 2015 to June 2016. As well as finding out what are the factors that lead to differences in the polio immunization coverage. This research was a descriptive research of secondary data as well as qualitative research conducted by doing the interview against the causes of babies who are not in immunization, with a total sampling technique by looking at the total number of babies in primary care. From the existing data calculation then found the number of Polio immunization coverage in the rural health centers amounted to 92.7%, while in urban public health center amounted to 96.32%. As well as some of the factors that affect : immunization services, in which the social economy, the displacement of population, level of knowledge, the refusal of immunization, vaccine false news, the motivation of the mother, family and community support. There are differences Polio immunization coverage in infants between rural and urban health centers in Sukoharjo, with differences in polio immunization coverage in urban areas that are larger compared polio immunization coverage in rural areas.